pelatihan Menggambar dan Mewarnai Menggunakan Microsoft Paint untuk meningkatkan kreativitas anak-anak - Selviyani; Harma Oktafia Lingga Wijaya; Elmayati; Wisdalia Maya Sari; Joni Karman; Rani Purnama Aprisusanti (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
This community service activity (PKM) was carried out with the aim of providing an understanding of the importance of technology, as well as providing training to improve basic skills and the use of fundamental computer applications, such as Paint, to the children of the Muara branch kel. Belalau II City of Lubuklinggau. The method of implementing this activity is carried out using the lecture and discussion method between participants and presenters, as well as how to combine children's interest in drawing with today's rapid technological developments so that children can improve their drawing skills with current technological developments. The result of this activity is an increase in participants' understanding of the basics of computer operation and participants' skills in using fundamental computer applications, including the use of the paint application as a tool for making drawings